THE INFLUENCE OF E-MODULE BASED ON ROLE-PLAYING LEARNING MODEL WITH SCIENTIFIC APPROACH AND CULTURALLY RESPONSIVE TEACHING TO 10TH GRADERS’ QUANTITY AND MEASUREMENT CONCEPTUAL MASTERY - Martha, Christina; Laksmisari, Rusna; Munfaridah, Nuril (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2023)
Physics is a fundamental science that is essential to master, particularly the skill of measuring quantities in daily life. This study aims to analyze the influence of an e-module based on a role-playing learning model with a scientific approach and culturally responsive teaching on 10th graders' conceptual mastery of quantity and measurement. The study was conducted using two cycles of Kurt Lewin's Class Action Research Cycle. The implementation of this learning innovation used a sample of 27 students fromclass X-11 at SMAN 9 Malang. The e-module learning media is based on a role-playing learning model with a scientific approach and culturally responsive teaching. This approach was found to increase students' conceptual mastery in magnitude and measurementin class X-11 at SMAN 9 Malang. The percentage of passing scores increased from 30% after Cycle I to 70% after Cycle II. This e-learning module is based on a role-playing model with a scientific approach and culturally responsive teaching. It has been found to improve students' conceptual mastery in quantity and measurementin class X-11 at SMAN 9 Malang.